"C–H⋯π Interaction" regulates the stereoselectivity in olefin polymerization. Issue 47 (15th May 2019) - Zhao, Yanan; Luo, Gen; Kang, Xiaohui; Guo, Fang; Zhu, Xuefeng; Zheng, Rencheng; Hou, Zhaomin; Luo, Yi
Abstract : DFT calculations reveal that a coordinating THF plays an essential role in regulating the stereoselectivity via C–H⋯π noncovalent interaction. Abstract : DFT calculations disclosed that the stereoselectivity of Sc-catalysed polymerization of halogenated styrenes could be co-regulated via C–H⋯π interactions between a coordinating THF and the phenyl ring of a monomer. Such a regulatory mechanism was theoretically confirmed by further studying the polymerization of various monomers, where the stereoselectivity could even shift from syndiotacticity to isotacticity.